EXPLORING THE INSTRUCTION’S IMPACTS ON STUDENTS’ GRAMMATICAL ERRORS IN INTERNET-MEDIATED COMMUNICATION - Fuyudloturrohmaniyyah, Ni'mal (International Journal of Education, 2018)
Since its emergence in Second Language Acquisition (SLA), proposed by Selinker in 1972, massive studies of interlanguage have been carried out in numerous EFL/ESL classrooms as it is worth researching to gain plausible factors which either facilitate the TL learning or make it suffers. Therefore, this study attempts to see the impact of English course instruction on a student’s interlanguage. The data are grammatical errors made by the student during internet-mediated texting which were later on analyzed qualitatively. The result shows that structurally all the errors are caused by direct translation from the student’s native language, Indonesian, to English. This phenomenon seems to be predictable, as during the instruction the student is provided barely with English sentences which differ from Indonesian structure. Therefore, it is expected that the teachers as well as the institution redesign the content of learning to expose students to English which might be different from Indonesian, yet will be very crucial to establish satisfying communicative competence.